Development and characterization of probiotic fermented smoothie beverage - Gallina, Darlila; Barbosa, Paula; Ormenese, Rita de Cássia; Garcia, Aline (Revista Ciência Agronômica, 2019)
Dairy products are the primary delivery for probiotics, with great popularity among the public looking for functional foods. The addition of probiotics to new food matrices requires studies about the stability and viability of these microorganisms in the final product. This study aimed to develop a probiotic smoothie beverage and to evaluate the microbiological quality, pH, acidity, syneresis, probiotics viability, sensory acceptance, and consumers’ preference. For that, thirty-six beverage formulations were prepared using yogurt and different fruit pulps. Six formulations were selected for the study, as follows: probiotic yogurt with the addition of mango pulp, grape, red fruits (containing 8 and 10% sucrose), mango/passion fruit, and red fruits/açaí, using a yogurt/pulp ratio of 60/40 (w/w). The beverages presented adequate hygienic-sanitary quality, with an initial probiotics viability around 7 log CFU mL-1. An increase in acidity and a decrease in pH, as well as a higher rate of syneresis and a small decline in probiotic viability were observed for all formulations throughout 30 days of storage. The probiotic smoothie made with red fruit pulp (10% sugar) was selected due to its better sensory acceptance, and maintenance of probiotic counts to confer health benefits.